Comparative genomics : international workshop, RECOMB-CG 2009, Budapest, Hungary, September 27-29, 2009 : proceedings - Sorin Istrail, Pavel Pevzner, Michael S. Waterman, Craig E. Nelson, Stéphane Vialette. (Springer, 2017)
275p.